Belgium : Technical Note on Financial Conglomerate Supervision. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
Belgian financial conglomerates (FCs) remained important players in the Belgian financial sector, despite significant restructuring following the global financial crisis. FCs operated in multiple streams of the financial sector, especially in banking and insurance. Owing to their economic reach and use of regulated and unregulated entities across sectoral boundaries, FCs presented a challenge for sector-specific supervisory oversight. The Executive Board suggested a pragmatic supervisory approach, which needs to be streamlined and applied more uniformly to contain FC-specific risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet